The healing myocardium mobilizes a distinct B-cell subset through a CXCL13-CXCR5-dependent mechanism. Issue 13 (28th May 2021) - Heinrichs, Margarete; Ashour, DiyaaElDin; Siegel, Johanna; Büchner, Lotte; Wedekind, Georg; Heinze, Katrin G; Arampatzi, Panagiota; Saliba, Antoine-Emmanuel; Cochain, Clement; Hofmann, Ulrich; Frantz, Stefan; Campos Ramos, Gustavo
Abstract: Aims: Recent studies have revealed that B cells and antibodies can influence inflammation and remodelling following a myocardial infarction (MI) and culminating in heart failure—but the mechanisms underlying these observations remain elusive. We therefore conducted in mice a deep phenotyping of the post-MI B-cell responses in infarcted hearts and mediastinal lymph nodes, which drain the myocardium. Thereby, we sought to dissect the mechanisms controlling B-cell mobilization and activity in situ. Methods and results: Histological, flow cytometry, and single-cell RNA-sequencing (scRNA-seq) analyses revealed a rapid accumulation of diverse B-cell subsets in infarcted murine hearts, paralleled by mild clonal expansion of germinal centre B cells in the mediastinal lymph nodes. The repertoire of cardiac B cells was largely polyclonal and showed no sign of antigen-driven clonal expansion. Instead, it included a distinct subset exclusively found in the heart, herein termed 'heart-associated B cells' (hB) that expressed high levels of Cd69 as an activation marker, C-C-chemokine receptor type 7 ( Ccr7 ), CXC-chemokine receptor type 5 ( Cxcr5 ), and transforming growth factor beta 1 ( Tgfb1 ). This distinct signature was not shared with any other cell population in the healing myocardium. Moreover, we detected a myocardial gradient of CXC-motif chemokine ligand 13 (CXCL13, the ligand of CXCR5) on Days 1 and 5 post-MI. When compared with wild-type controls, mice treated with a neutralizing CXCL13-specific antibody as well as CXCR5-deficient mice showed reduced post-MI infiltration of B cells and reduced local Tgfb1 expression but no differences in contractile function nor myocardial morphology were observed between groups. Conclusion: Our study reveals that polyclonal B cells showing no sign of antigen-specificity readily infiltrate the heart after MI via the CXCL13-CXCR5 axis and contribute to local TGF-ß1 production. The local B-cell responses are paralleled by mild antigen-driven germinal centre reactions in the mediastinal lymph nodes that might ultimately lead to the production of specific antibodies. Graphical Abstract: